2015
DOI: 10.2215/cjn.10181014
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Preparedness and Awareness of Patients on Hemodialysis after Hurricane Sandy

Abstract: Background and objectives Patients with ESRD on dialysis live in a complex sociomedical situation and are dependent on technology and infrastructure, such as transportation, electricity, and water, to sustain their lives. Interruptions of this infrastructure by natural disasters can result in devastating outcomes.Design, setting, participants, & measurements Between November of 2013 and April of 2014, a cross-sectional survey was conducted of patients who received maintenance hemodialysis before and after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…Other studies have also investigated the impact of natural disasters on patient care. [8][9][10][11][12][13] One study showed that timely deployment of emergency team and preparedness plan greatly assisted in the effectiveness of care delivery for patients. 8 Furthermore, the lack of preventable errors at hospitals can be attributable to strategic planning.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also investigated the impact of natural disasters on patient care. [8][9][10][11][12][13] One study showed that timely deployment of emergency team and preparedness plan greatly assisted in the effectiveness of care delivery for patients. 8 Furthermore, the lack of preventable errors at hospitals can be attributable to strategic planning.…”
Section: Discussionmentioning
confidence: 99%
“…Our final instrument included five items: Do you know where there is another dialysis facility if the facility that provides your in‐center dialysis is damaged by an earthquake? Do you know how to control dietary intake when you may not be able to take dialysis during a week because of the collapse of all dialysis facilities in your local area? Do you have information networks to find out available dialysis facilities at the time when you face an earthquake?…”
Section: Methodsmentioning
confidence: 99%
“…Thorough preparation for natural disasters by national government, local government, dialysis centers, and patients can mitigate disaster influences . Previous studies have shown that disaster preparedness by hemodialysis patients is likely to mitigate missed dialysis sessions , and reduce comorbidity from depression and PTSD after disasters . However, our review showed that only a few previous studies have investigated the levels of disaster preparedness and the related factors that might affect this in hemodialysis patients .…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…17,18 A considerable literature has described the principles of disaster management for renal patients. 3,[18][19][20][21][22][23][24][25][26] Reports have included guidance for predisaster planning, strategies for the evaluation and treatment of patients, and management of dialysis-related issues. Other issues addressed include coordinating relief efforts, setting of priorities, resolving logistical issues, and recognizing pitfalls to be avoided.…”
mentioning
confidence: 99%